In Vivo Digestion of Egg Products Enriched with DHA: Effect of the Food Matrix on DHA Bioavailability - Carlos Pineda-Vadillo (Foods, 2021)
The aim of the present study was to determine to what extent the food matrix could affect the release of docosahexaenoic acid (DHA) during digestion and its incorporation into systemic circulation. In this aim, three DHA-enriched egg products having the same composition but different structure were developed: omelet, hard-boiled egg, and mousse. Then, nine pigs fitted with T-shape cannulas at duodenal level and a jugular venous catheter were fed with the DHA-enriched egg products, and duodenal effluents and plasma were collected throughout the postprandial period. Results highlighted an undeniable effect of the food matrix on digestion parameters and DHA bioavailability. The transit of DHA and protein through the duodenum was faster after the ingestion of the mousse than after the ingestion of the omelet and hard-boiled egg. While most of the DHA and protein ingested under the form of mousse had already passed through the duodenum 4.5 h after its ingestion, significantly higher quantities were still present in the case of the omelet and hard-boiled egg. In terms of bioavailability, the omelet was the most efficient vector for delivering DHA into systemic circulation. It supplied 56% and 120% more DHA than the hard-boiled egg and the mousse, respectively.